2002
DOI: 10.1101/gr.670002
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Embryo-Derived Stem Cells Reveals Candidate Genes Associated With Pluripotency and Lineage Specificity

Abstract: Large-scale gene expression profiling was performed on embryo-derived stem cell lines to identify molecular signatures of pluripotency and lineage specificity. Analysis of pluripotent embryonic stem (ES) cells, extraembryonic-restricted trophoblast stem (TS) cells, and terminally-differentiated mouse embryo fibroblast (MEF) cells identified expression profiles unique to each cell type, as well as genes common only to ES and TS cells. Whereas most of the MEF-specific genes had been characterized previously, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
156
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(169 citation statements)
references
References 38 publications
12
156
0
1
Order By: Relevance
“…We then attempted to identify candidate genes that are expressed more highly in the ICM than in TE cells. Due to difficulty of collecting the ICM and TE from blastocysts separately, we exploited the cultured cells derived from these cell types in our previous study (Tanaka et al, 2002). Mouse ES cells are cultured from the ICM (Evans and Kaufman, 1981;Martin, 1981), whereas mouse TS cells are cultured from the TE (Tanaka et al, 1998) (Fig.…”
Section: Informatics Selection Of Candidate Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…We then attempted to identify candidate genes that are expressed more highly in the ICM than in TE cells. Due to difficulty of collecting the ICM and TE from blastocysts separately, we exploited the cultured cells derived from these cell types in our previous study (Tanaka et al, 2002). Mouse ES cells are cultured from the ICM (Evans and Kaufman, 1981;Martin, 1981), whereas mouse TS cells are cultured from the TE (Tanaka et al, 1998) (Fig.…”
Section: Informatics Selection Of Candidate Genesmentioning
confidence: 99%
“…To supplement the data (Tanaka et al, 2002) and update to the latest microarray platform, we performed hybridizations of ES and TS RNAs onto the NIA 22K 60-mer oligonucleotide microarrays in triplicate (Carter et al, 2003a). This glass-slide microarray platform contains genes from preimplantation and stem cells (for experimental design, see ref (Tanaka et al, 2002); for all the array data set, see http://lgsun.grc.nia.nih.gov/data, and also Supplementary Material 3).…”
Section: Informatics Selection Of Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous reports have suggested that Esg1 is not expressed after the preimplantation and peri-implantation stages [11,12], we examined Esg1 expression during germ cell development. A unique quality of segregating PGCs is the expression of many pluripotency-associated genes, which are downregulated in somatic cells.…”
Section: Esg1 Oct4 and Sox2 Coexpression In Es And Germ Cellsmentioning
confidence: 99%
“…For example, during erythropoiesis nuclei become smaller and heterochromatic as many genes are silenced; concurrently, globin genes become active by associating with specific nuclear sites known as "factories" or "active chromatin hubs" (Cook, 1999(Cook, , 2002de Laat and Grosveld, 2003;Osborne et al, 2004). Although microarrays provide detailed information on changes in steady-state mRNA levels during differentiation (Kelly and Rizzino, 2000;Harris and Childs, 2002;Tanaka et al, 2002;Sperger et al, 2003), there is little information on how primary rates of transcription change. For example, we do not know by how much global rates vary as any mammalian cell differentiates.…”
mentioning
confidence: 99%